Growth factors and the importance of the shadow economy in African countries - T. F. Alhassan; T. K. Blokhina (Управление)
The factors, causing the rapid expansion of the shadow economy (informal economy) in developing countries, especially in sub-Saharan Africa have been considered in the article. The shadow economic sector is the largest and fast growing sector in the region, therefore, it is necessary to study and make policy recommendations for development. The authors have studied some definitions of the shadow economy of well-known authors and outlined the essence and background of these definitions. Furthermore, the factors, dragging the development of the sector have been considered. The reasons behind low financial access among these enterprises have been studied. It has been revealed, that information asymmetry is one of the main problems, which limits access to finance by firms of the shadow economy. Consequently, small, (lower) access to finance limits the innovation activities of small and medium-sized enterprises, through which these firms produce goods and services to address (meet) local needs.However, the role of the shadow economy cannot be overlooked as the sector provides more than 55 % of employ and also contributes more than 50 % of the region’s gross domestic product. Thus, it is more able to stifle small and medium-sized enterprises in the informal sector of the economy and their innovative projects, which can slow down the technological industrialization and economic development of the region. The author’s position on measures to solve the problems of financial accessibility and access of shadow small and medium-sized enterprises to financial resources in the region has been substantiated. Thus, there is need of great attention of policy makers and the business community in tackling the problems, designated in this article, because it contributes to the economic and innovative development of the region.